2013
DOI: 10.3136/fstr.19.113
|View full text |Cite
|
Sign up to set email alerts
|

Oleanolic Acid and Ursolic Acid in Commercial Dried Fruits

Abstract: Oleanolic acid (OA) and ursolic acid (UA) are natural triterpenoids that have preventive properties such as anti-tumor and anti-hepatitis activities. These triterpenes are known to exist in several medicinal plants and fruit skins. Dried fruits are usually eaten without removing the skin; thus, they may be good resources for oral intake of OA and UA. HPLC analysis of OA and UA contents in a variety of dried fruits showed that raisins contained higher levels of OA than the other fruits investigated, with green … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 14 publications
1
10
0
Order By: Relevance
“…Therefore, oleanolic acid content is much higher in fruit “skin” or “peel” (non-botanical terms which include cuticle and multiple cell types) in comparison with the pulp (Table 1). In general, fruits which are consumed with the skin, including dried fruits, can be better dietary sources of oleanolic acid [26]. The most important sources of oleanolic acid in human diet are olives ( Olea europaea L.), from which the compound derives its name, and their products, such as olive oil [27].…”
Section: Sources and Bioavailabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, oleanolic acid content is much higher in fruit “skin” or “peel” (non-botanical terms which include cuticle and multiple cell types) in comparison with the pulp (Table 1). In general, fruits which are consumed with the skin, including dried fruits, can be better dietary sources of oleanolic acid [26]. The most important sources of oleanolic acid in human diet are olives ( Olea europaea L.), from which the compound derives its name, and their products, such as olive oil [27].…”
Section: Sources and Bioavailabilitymentioning
confidence: 99%
“…Comparative analysis of 38 commercial herbal extracts showed the presence of oleanolic acid in extracts of Aesculus hyppocastanum L., Crataegus monogyna L., Harpagophytum procumbens DC, Lagerstroemia speciosa L., Ortosiphon stamineus L., Punica granatum L., Styrax benzoin Dryand., Vaccinium myrtillus L. and Vitis vinifera L. [37]. Oleanolic acid is also detected in propolis [37] and numerous plant-based products, including spices [38,39], vegetable oil [27], and snack products, containing dried whole fruits [26]. …”
Section: Sources and Bioavailabilitymentioning
confidence: 99%
“…On the other hand, it has been demonstrated that UA has been safely used as a daily dietary supplement, without toxic events [40][41][42]. It is worth remembering that UA is naturally synthesized by different fruits and vegetables present in the human diet [43]; therefore, UA toxicity may be related to the dosage, formulation, duration of treatment and route of administration.…”
Section: Discussionmentioning
confidence: 99%
“…can also be used as sources of triterpenes. Dried Vitis vinifera berries have been found to contain up to 79.0 mg/100 g of OA, meanwhile, dried cranberries or blueberries contained both OA and UA (17.8 and 65.5 mg/100 g or 13.9 and 11.8 mg/100 g, respectively) [ 40 ].…”
Section: Chemistry Occurrence and Isolation Of Ursolic And Oleanolic Acidsmentioning
confidence: 99%